CORRELATION BETWEEN POPULATION DENSITY, CURE RATE, MORTALITY RATE WITH TB AFB+ INCIDENCE IN SURABAYA 2018-2020: Korelasi Antara Kepadatan Penduduk, Angka Kesembuhan, Angka Kematian Dengan Kejadian TB BTA+ Di Surabaya 2018-2020 - Laura Nadya Damayanty Agusputri; Lucia Yovita Hendrati (Universitas Airlangga, 2023)
Background: In 2020, the World Health Organization (WHO) stated that as many as 10 million people suffered from tuberculosis and 1.5 million died, making it the 13th cause of death in the world's top infectious killer number two after COVID-19. The incidence of Acid-fast bacillus (AFB)+ Tuberculosis TB in Surabaya increased from 2018 to 2020. Purpose: This study aimed to describe the distribution of TB AFB+ incidence in Surabaya by mapping and to analyze the relationship between population density, TB AFB+ cure rates, and death rates during TB AFB+ treatment with AFB + TB incidence in 31 sub-districts of Surabaya City from 2018 to 2020. Methods: This was a descriptive study with secondary data processing obtained from the Surabaya Health Profile Book 2018-2020 using the Pearson Correlation Product Moment statistical test. Results: There was a correlation between population density and the incidence of TB AFB+ in 2018 (0.61), 2019 (0.65), and 2020 (0.62). Then there was a correlation between TB AFB+ cure rate and TB AFB+ incidence in 2018 (0.98), 2019 (0.96), and 2020 (0.91). There was a correlation between the mortality rate during TB AFB+ treatment and the incidence of TB AFB+ in 2018 (0.31), 2019 (0.71), and 2020 (0.88). Conclusion: There is a relationship between population density, TB AFB + cure rate, the mortality rate during AFB + TB treatment, and the incidence of AFB + TB in Surabaya.